2021
DOI: 10.3389/fphar.2021.675999
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicines and Active Metabolites: Potential Antioxidant Treatments for Atherosclerosis

Abstract: Atherosclerosis is a complex chronic disease that occurs in the arterial wall. Oxidative stress plays a crucial role in the occurrence and progression of atherosclerotic plaques. The dominance of oxidative stress over antioxidative capacity generates excess reactive oxygen species, leading to dysfunctions of the endothelium and accelerating atherosclerotic plaque progression. Studies showed that Chinese herbal medicines and traditional Chinese medicine (TCM) might regulate oxidative stress; they have already b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 205 publications
(211 reference statements)
0
5
0
1
Order By: Relevance
“…After balancing oxidation and antioxidation, NO and eNOS bioavailability improved, reducing inflammation, autophagy, and apoptosis, and inhibiting the recruitment of monocytes by adhesion factors, thereby protecting endothelial cell function. By elevating high-density lipoprotein (HDL) cholesterol absorption capacity, quercetin increased HDL antioxidation and reduced lipid accumulation [22]. GBE is a multifunctional neuroprotective agent and decreases post-ischemia-reperfusion injury stress [23].…”
Section: Discussionmentioning
confidence: 99%
“…After balancing oxidation and antioxidation, NO and eNOS bioavailability improved, reducing inflammation, autophagy, and apoptosis, and inhibiting the recruitment of monocytes by adhesion factors, thereby protecting endothelial cell function. By elevating high-density lipoprotein (HDL) cholesterol absorption capacity, quercetin increased HDL antioxidation and reduced lipid accumulation [22]. GBE is a multifunctional neuroprotective agent and decreases post-ischemia-reperfusion injury stress [23].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis (AS) is also a severe disease that can cause vascular damage [ 120 , 121 ]. Although many drugs can treat atherosclerosis [ 122 , 123 , 124 ], their systemic administration has serious disadvantages. In particular, the proportion of therapeutic dose reaching atherosclerotic lesions is small, resulting in poor therapeutic effect.…”
Section: Mnps For Vascular Repairmentioning
confidence: 99%
“…Moreover, oxidative stress can activate inflammatory mediators, leading to the development of metabolic and inflammatory diseases [ 4 ]. Studies have shown that the mechanisms of action of many natural plants in the treatment of chronic diseases are closely related to antioxidant function [ 5 ]. In China, there is a special class of natural plant raw materials that not only have the nutritional ingredients of ordinary food and can be used as diet but also have the functional ingredients of medicine and can be used as medicine.…”
Section: Introductionmentioning
confidence: 99%